ANALISIS KESULITAN MEMBACA PERMULAAN SISWA KELAS II SDN 42 LUBUKLINGGAU - Asti Kurnia Dewi Saputri; Deka Yuliana Audiya; Episiasi (JIP: Jurnal Ilmu Pendidikan, 2025)
Helping learn The most frequently encountered elementary school students are difficulties in learning to read. In class II students at SD Negeri 42 Lubuklinggau, this problem was also found, so this research aims to describe students' initial reading difficulties. This research uses descriptive qualitative research methods. The subjects of this research included 8 students who had difficulty reading, the class teacher, and 8 students' parents. Observations, interviews, and document analysis were used to collect data. Test the validity of the data using data triangulation and techniques. Data analysis techniques use data collection, data reduction, data presentation, and drawing conclusions. helping class II students at SD Negeri 42 Lubuklinggau experienced by 8 students. The first support is difficulty in recognizing letters, there are 2 students who don't know letters from A to Z. The second support is difficulty in reading diphthong letters, there are 2 students who don't want to pronounce any letters or get stuck when reading diphthong letters. The third is difficulty in reading words, there are 4 students who are not yet fluent in reading words or are still spelling them. students who are still not fluent in reading sentences. As a class teacher, it is hoped that they can understand the characteristics of students well so that they are able to solve problems well and appropriately. It can be concluded that the difficulties experienced by these 8 students varied.